Racial Disparities in Low PAPP-A Levels and Pregnancy Outcomes [29H]. (May 2018) - Shand, Muhammed F.; Gimovsky, Alexis; Macri, Charles
Abstract : INTRODUCTION: Pregnancy-associated plasma protein A(PAPP-A) is associated with adverse pregnancy outcomes: preterm birth, growth restriction, stillbirth and preeclampsia. The association of low PAPP-A and pregnancy outcomes based on race is unknown. The objective of this study was to determine if low PAPP-A is associated with labor dysfunction in different racial populations. METHODS: Retrospective study of pregnant women with PAPP-A ⩽5%ile between 7/2013-7/2016. Outcomes of non-Hispanic white (NHW) women were compared to non-Hispanic black (NHB) women. Primary outcome: cesarean delivery (CD) rate. Secondary outcomes: indication for CD, perinatal outcomes. Exclusion: women with fetuses with known or suspected aneuploidy. RESULTS: 114 women were included; 69 NHW women and 45 NHB women. Demographical differences included maternal age at delivery (35.0 ± 4.1 weeks in the NHW group vs.30.5 ± 5.6 in the NHB group, p<0.001), gravidity (1.9 ± 1.3 in the NHW group vs. 3.1 ± 1.9 in the NHB group, p<0.001), parity (0.5 ± 0.7 in the NHW group vs. 1.1 ± 1.3 in the NHB group, p=0.002), and BMI (28.7 ± 4.9 in the NHW group vs. 34.3 ± 9.1 in the NHB group, p<0.001). There was no difference noted in CD rate (18/69(26.1%) vs. 13/45(28.9%), p=0.6) or fetal indication for CD (5/18(29.6%) vs. 4/13(33.3%), p=0.9). Neonatal morbidity composite score was different between groups (12/69, 17.4% in the NHW group vs. 20/45, 44.4% in the NHB group, p=0.002). CONCLUSION: No racial association with delivery mode or indication for cesarean delivery. Increased neonatal morbidity during labor noted among NHB women with low PAPP-A.